Re-Configuring Identity Postpartum and Sustained Abstinence or Relapse to Tobacco Smoking - Brown, Tracey J. (Int J Environ Res Public Health, 2019)
Relapse to smoking postpartum is a common and important public health problem. Difficulty in adjusting to a non-smoking identity is a key factor prompting relapse. However, postpartum relapse prevention interventions rarely focus upon offering support for identity change. We conducted an exploratory inductive analysis of a dataset from the Prevention of Return to Smoking Postpartum (PReS) study to understand identity constructs and experiences of pre- and postpartum women (smokers and ex-smokers), partners and health professionals. Data were obtained from 77 unique participants via focus groups, interviews, email or online questionnaires, and were analyzed by two researchers independently, using NVivo 12. Four main themes emerged reflecting identity transition from the pre- to the postpartum period: (i) Pregnancy and the categorization of smoking status; (ii) the disruption of motherhood and loss of self; (iii) adapting to a maternal non-smoking identity; and (iv) factors influencing sustained abstinence versus relapse to smoking. Postpartum relapse prevention interventions need to consider support for women, and the whole family unit, in adjusting to a new identity as a non-smoking mother. Smoking status should be revisited throughout pregnancy and into the postpartum period to aid the long-term integration of smoke-free behavior.